Healthy babies for mothers with serious mental illness: A case management framework for mental health clinicians - Hauck, Yvonne; Rock, D.; Jackiewicz, T.; Jablensky, A. (Blackwell Publishing, 2008)
Women with a serious mental illness (SMI), notably schizophrenia, bipolar disorder and personality disorders are considered high risk for adverse pregnancy and birth outcomes, which in turn are associated with poor neurodevelopment in the child. Failure to access antenatal care, poor adherence with folate supplementation, an unhealthy lifestyle, and inappropriate health decisions can contribute to poor outcomes. Many women with SMI continue contact with mental health services while pregnant. This promary prevention project aimed to develop a framework for community mental health clinicians to improve the reproductive health outcomes for women with SMI. The consultation process involved discussions with key stakeholders, an environmental scan to determine current service delivery issues a literature review, and individual and group interviews with community mental health clinicians, consumers general practitioners and midwives. Three key elements underpin the framework: early detection and monitoring of pregnancy providing reproductive choices and implementing a 'small known team approach' in the management of the pregnant client. Specific modules within the framework focus upon establishing a professional support network, assessing the risk of pregnancy the early detection of pregnancy, monitoring during pregnancy, preparing for birth, and planning for the postnatal period. Implementation of the framework has the potential to significanty improve obstestric and neonatal outcomes for this high-risk group.